Allogenic umbilical cord tissue for temporomandibular joint injuries - Aratikatla, Adarsh; Ghandour, Samir; Maffulli, Nicola; Gupta, Manu; Gupta, Ashim (Frontiers in Pain Research, 2023)
The temporomandibular joint (TMJ) is crucial for functions of daily living such as mastication and articulation. Common TMJ issues include osteoarthritis, internal derangement, and myofascial pain dysfunction. Conservative methods such as physical therapy and medications are used, with surgical options such as arthroscopy and replacement for severe cases. Emerging regenerative medicine explores non-surgical treatments using human stem cells from umbilical cord derivatives, showing potential for tissue regeneration in TMJ disorders. A systematic search was conducted across PubMed, Embase, Scopus, and Web of Science databases, adhering to PRISMA guidelines, aiming to identify relevant articles published in English until August 2023. The search used specific terms to target in vitro, preclinical, and clinical studies on umbilical cord (UC)-derived tissue and mesenchymal stem cells (MSCs) for treating TMJ disorders. The search was extended to three clinical trial registries for on-going investigations related to UC tissue and MSCs for TMJ disorder management. The studies included in this article report the safety and efficacy profiles of allogenically acquired, umbilical cord-derived tissues and associated mesenchymal stem cells for temporomandibular joint ailments, future adequately powered, randomized controlled trials are warranted to conclusively justify the clinical use of this biologic therapy.